GAMBARAN PELEPASAN INFORMASI REKAM MEDIS VISUM ET REPERTUM DI RSUD H. ABDUL AZIZ MARABAHAN - Anshari, Muhammad Rashif; Natasya, Cindy (Jurnal Kajian Ilmiah Kesehatan dan Teknologi, 2025)
This study aims to describe the process of releasing medical record information (Visum et Repertum) at RSUD H. Abdul Aziz Marabahan. The methods used were observation and documentation during an internship at the Health Information Unit (Unit KIR) in January 2025. The findings indicate that the release workflow begins with receiving an official request letter from the authorized agency (police), followed by examination by a physician, drafting by medical records staff, verification and signing by the responsible physician and the Hospital Director, and final delivery exclusively to authorized parties. The main requirements include an official request letter, patient identification, and supporting documents. Obstacles encountered include illegible handwriting by physicians, lack of firmness in police collection of results, and delays in signing when specialist physicians are unavailable. The conclusion shows that the procedure is conducted in accordance with Standard Operating Procedure No. 445/010/XII/MRMIK-RSUD/2022, but improvements in coordination and a more comprehensive SOP are needed. Recommendations include refining the SOP, enhancing inter-party communication, and providing administrative training to make the information release process more effective and compliant with regulations